1992
DOI: 10.1002/elan.1140040405
|View full text |Cite
|
Sign up to set email alerts
|

Identification of photochemical products of amino acids, peptides, and proteins in on‐line, postcolumn photolytic derivatization detection by HPLC‐electrochemistry

Abstract: ABSTMCTIn previous studies we have developed a method for the electrochemical detection of aromatic amino acids, sulfur-containing amino acids, peptides, and proteins in HPLC by using photolytic derivatization approaches. Upon irradlation, nonelectroactive (or even inherently electroactive) amino acids and peptides can be converted to electroactive (or more electroactive) compounds, in an on-line, postcolumn manner, which can be detected electrochemically in HPLC. In the case of proteins, the same method can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The simultaneous measurement of monamines, metabolites, and amino acids in brain tissue and microdialysis perfusates was developed by Gamache and co-workers (F38), using HPLC with a coulometric array of graphite flow-through electrodes. Electrochemical detection of peptides and proteins was achieved with a postcolumn photochemical derivatization step, as reported by Krull and Dou (F39,F40), leading to the formation of electrochemically oxidizable photoproducts. Amperometric and fast-scan-rate cyclic voltammetry at a 10-jum-diameter platinum microelectrode were utilized by Soucaze-Guillous and co-workers (F41) for the detection and in situ identification of fullerenes which were separated by gel permeation HPLC.…”
Section: F Electrochemical Detectorsmentioning
confidence: 99%
“…The simultaneous measurement of monamines, metabolites, and amino acids in brain tissue and microdialysis perfusates was developed by Gamache and co-workers (F38), using HPLC with a coulometric array of graphite flow-through electrodes. Electrochemical detection of peptides and proteins was achieved with a postcolumn photochemical derivatization step, as reported by Krull and Dou (F39,F40), leading to the formation of electrochemically oxidizable photoproducts. Amperometric and fast-scan-rate cyclic voltammetry at a 10-jum-diameter platinum microelectrode were utilized by Soucaze-Guillous and co-workers (F41) for the detection and in situ identification of fullerenes which were separated by gel permeation HPLC.…”
Section: F Electrochemical Detectorsmentioning
confidence: 99%
“…It has been shown that some polypeptides can be detected by their free amino (NH,) group [38] or by the presence of the phenol group of tyrosine (tyr) or the indole group of tryptophan (trp) [39], methionine (met), and cysteine (cys). The use of photolytic reactions [35][36][37]431 and chemically modified electrodes [44] has extended the application of electrochemical detection [45]. Initial stuches showed that peptides could be detected by modifying them with electroactive substituents such as 3,G-dinitrophthalic anhydride [ 461.…”
mentioning
confidence: 99%